2014
DOI: 10.1186/1471-2180-14-199
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of probiotic surface layer protein-carrying Lactobacillus amylovorus strains

Abstract: BackgroundAdhesiveness to intestinal epithelium, beneficial immunomodulating effects and the production of pathogen-inhibitory compounds are generally considered as beneficial characteristics of probiotic organisms. We showed the potential health-promoting properties and the mechanisms of probiotic action of seven swine intestinal Lactobacillus amylovorus isolates plus the type strain (DSM 20531T) by investigating their adherence to porcine intestinal epithelial cells (IPEC-1) and mucus as well as the capaciti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 74 publications
1
40
0
Order By: Relevance
“…We also found that the processing of the signal peptide of the SlpA protein renders a 413-amino-acid mature protein beginning with the sequence ATTINA, as described for other Lactobacillus species (Lortal et al 1992;Vidgrén et al 1992;Sillanpää et al 2000;Ventura et al 2000;Sára and Sleytr 2000;Hynönen et al 2014).…”
Section: Discussionmentioning
confidence: 83%
“…We also found that the processing of the signal peptide of the SlpA protein renders a 413-amino-acid mature protein beginning with the sequence ATTINA, as described for other Lactobacillus species (Lortal et al 1992;Vidgrén et al 1992;Sillanpää et al 2000;Ventura et al 2000;Sára and Sleytr 2000;Hynönen et al 2014).…”
Section: Discussionmentioning
confidence: 83%
“…Previously, we monitored lactic acid bacteria (LAB) population during spontaneous fermentation of the Brassica oleracea var. capitata cultivar Varaždinski (Banić et al, 2018;Beganović et al, 2014;Beganović et al, 2011). At the onset of the spontaneous fermentation, LAB diversity was present, including Leuconostoc mesenteroides strains, while a restricted number of Lactobacillus species, mainly Lactobacillus plantarum, dominated in the latter stages (Beganović et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…brevis SF9B was isolated from the respective spontaneous fermentation. This strain showed desirable functional and technological properties largely influenced by S-layer proteins (Slps) which were detected by SDS-PAGE (Beganović et al, 2014) and identified by 2D electrophoresis followed by LC-MS analysis. Slps have a functional role in conveying increased survival of the respective strain in simulated GIT conditions and during freeze-drying.…”
Section: Introductionmentioning
confidence: 99%
“…features of Lactobacillus strains can be interesting factor to S-layer of these bacteria [5][6][7]. Some biochemical properties of Lactobacillus S-layer are unique compared with S-layer of other bacteria, for example in their smaller size (25-71 kDa) and high predicted pI value (9.4-10.4).…”
mentioning
confidence: 99%
“…SDS-PAGE analysis. Lanes(4,6), Total protein from untreated cells, (3,7) primary LiCl extracted S-layer, (2,8) Total protein from treated cells, (1,9) secondary LiCl extracted S-layer (1,9) from two strains, L. brevis KM7 and brevis KM3 respectively and (5) protein marker.…”
mentioning
confidence: 99%